Cruz Andreotti, G. (ed.), Roman Turdetania: Romanization, Identity and Socio-Cultural Interaction in the South of the Iberian Peninsula between the 4th and 1st centuries BCE. - Albuquerque, Pedro (SPAL - Revista de Prehistoria y Arqueología, 2019)
Cruz Andreotti, G. (ed.), Roman Turdetania: Romanization, Identity and Socio-Cultural Interaction in the South of the Iberian Peninsula between the 4th and 1st centuries BCE. Leiden, Boston, Brill, 2019